Genetic Variants in Interleukin-10 Gene Association with Susceptibility and Cervical Cancer Development: A Case Control Study - Pratap, Pushpendra D.; Raza, Syed Tasleem; Zaidi, Ghazala; Kunwar, Shipra; Ahmad, Sharique; Charles, Mark Rector; Eba, Ale; Rajput, Muneshwar (Global Medical Genetics, 2022)
Objectives Cervical cancer (CC) is one of the most destructive disease caused by persistent HPV infection which affects women worldwide, especially in developing countries. The genetic basis of host immune response especially cytokine function has been shown to influence CC susceptibility. Studies have demonstrated that IL-10 gene polymorphism have been associated with numerous malignancies, but in context to CC results were inconclusive. Though, aim of our study to investigate the association between IL-10 -1082A/G and -819C/T promoter polymorphism and CC susceptibility.Material and Methods This study comprised 192 women with CC and 200 controls. HPV detection was done by RT-PCR and genotyping was assessed through PCR-RFLP method. Serum concentration of IL-10 measured by ELISA.Results Women with AG and AG+GG genotypes of IL-10 -1082A/G had two-fold increased risk of CC [OR, 2.35 (95% CI, 1.54–3.58), p = 0.005], [OR, 2.03 (95% CI, 1.36–3.04), p = 0.0005] compared to controls. Women with G allele of -1082A/G polymorphism had linked with CC susceptibility [OR, 1.39 (95% CI, 1.02–1.88), p = 0.036] compared to controls. No significant difference was found between patients and controls in the genotype or allele frequencies of IL–10 -819C/T polymorphism [OR, 1.00 (95% CI, 0.63–1.58), p = 0.99]. The level of serum concentration of IL-10 was significantly higher in cases compared to controls.Conclusion These findings help to understand that polymorphism of IL-10 -1082A/G gene is associated with increased risk of CC development and can serve as a marker of genetic susceptibility to CC.
Keywords: human papillomavirus; cervical cancer; gene polymorphism